Program Edukasi Karakter, Kesehatan, dan Kebencanaan di Desa Purwabakti - Nuraeni, Prasasti; Anwar, Syaiful; Muhlis, Muhlis; Anggraeni, Novita; Khoirunnisa, Darin Hanifah (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to enhance the knowledge, awareness, and skills of the community through educational and participatory approaches to foster quality character, environmental care, health, and disaster preparedness. The program includes teaching noble character values, education on sorting organic and non-organic waste, basic health checks (blood pressure, blood sugar, weight, and height), disaster education, and craft-making activities to develop creativity. Implementation methods involve counseling, direct practice, and mentoring. The results show increased community understanding of noble character values, waste management, health awareness, and disaster preparedness. This activity is important for contributing positively to building a better and more sustainable society.